Description of a new species of the genus Maua Distant (Hemiptera, Cicadidae) from China - Wang, Jiali; Duffels, Joannes P.; Wei, Cong (Zootaxa, 2021)
A new species, Maua squeala sp. nov., is described from China. This species is similar to M. affinis Distant, 1905 and M. palawanensis Duffels, 2009, but can be distinguished by the shorter and more slender body of the new species, the lateral fasciae on the mesonotum and the shape of the male genitalia. The intraspecific variation of this species is discussed based on morphological observation combined with sequences of partial mitochondrial COI gene (DNA barcoding) of individuals exhibiting different morphological characters.